Where is the chiral critical point in 3-flavor QCD? - Chris Allton (Nuclear Physics B - Proceedings Supplements, 2004)
We determine the location of the second order endpoint of the line of first order chiral phase transition in 3-flavor QCD at vanishing chemical potential. Using Ferrenberg-Swendsen reweighting for two values of the quark mass we determine the dependence of the transition line on the chemical potential and locate the chiral critical point. For both quantities we find a significant quark mass dependence.